Design and development of broiler farm dashboard: enhancing farm management decision-making and performance measurement - Muhammad Farhan Hidayat; Winda Cahyo (Jurnal Sistem dan Manajemen Industri, 2023)
The poultry sector supplies over 65% of all animal protein and employs around 12 million people, or 10% of the workforce. About 85% of the broiler sector is dominated by the partnership structure. Although the core plasma partnership is one answer to the paucity of resources (financial, technical, and human), the partnership system has resulted in several issues: the dependence of plasma farmers on their partner management firm renders their bargaining position with the leading corporation weak. On the other hand, broiler farmers had limited records regarding their farming activities and financial costs, hindering their ability to assess their overall performance thoroughly. Furthermore, most prior broiler farm studies focused only on comparing a specific treatment effect on the single farm performance. Therefore, research on measuring various farm performances is essential. In order to provide a solution for manual accounting, it is necessary to implement an information system. The study focused on constructing dashboards for farm management and performance measurement of broiler farmers. Even more, the previous dashboard development study rarely focused on broiler farms. The dashboard is expected to provide independence in bookkeeping, maximize present farming cycle profit, and measure future performance. The self-service business intelligence methodology was utilized to create and construct the dashboard. Based on the findings, five dashboards were developed, each providing an extensive overview of the history of all farming periods, red, amber, and green analysis, all farming performance, and harvest setting for maximizing profit.